PENINGKATAN KUALITAS DAN KAPASITAS PRODUKSI CERIPING SINGKONG DAN PISANG MELALUI PENGGUNAAN ALAT PENGIRIS OTOMATIS - Nugraheni, Mutiara; Handayani, Titin Hera Widi; Utama, Agung (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2019)
Community empowerment aims to solve the problems faced by farmers groups Wulu Wetu and groups of women farmers Gotong Royong. The goals were, first, conducting education and training activities of the transfer of appropriate technology and entrepreneurship "(Entrepreneurship), namely education and training with diversified products of processed-based cassava and bananas; education and human resource management training; provide training in production management; Marketing management training; Entrepreneurial training. Second, perform the mentoring and coaching. The results of the implemented of community empowerment included a description associated with the selection of raw materials, material handling, processing, packaging, and marketing. The use of automatic slicer machine drive change production capacity, product characteristics and range of marketing after implemented the evaluation skills of community empowerment program for participants indicate that participants have understood the use of the automatic slicer equipment and processing cassava and banana into chips. The chances of developing the chips cassava and bananas are huge given area Pringombo is a producer of bananas and cassava, as well as supported by the vast potential market outside of Pringombo.